Beyond Non-Satiation: Needs and Requirements - Anna Pettini (Center for Economic Studies and ifo Institute (CESifo), 2014)
The hypothesis of non-satiation of rational choice theory is very seldom posed under scrutiny, maybe because it is taken as an anthropologic reality. Looking closer to that, we discover that it is taken for granted only in economic theory, and that it has become a reality as a result of a cultural process. This paper makes a brief story of this axiom, and looks at how it recently shifted into a modification of the original concept of adaptation. Using theoretical research in psychology, we find out that non-satiation is indeed not a natural feature of human beings, but a challenge to their happiness and a potentially pathological sign. The distinction between needs and requirements provides a new and solid ground on which we can discuss the quality of human needs, which is, according to Keynes, a key concept to define what the economic problem' is.
Keywords: D01; D11; D69; I31; I39; 330; non-satiation; needs; requirements; happiness; choice; adaptation; economic problem